Validity and reliability of local endemic language version of the SARI Sigma Scale questionnaire for assessing stigma in leprosy patients - Rahayu, Tri; Friska, Dewi; Sopamena, Yoslien; Menaldi, Sri Linuwih; Gibran, Kahlil; Dadun,; Ruwaida, Ida; Irawati, Yunia (Frontiers in Public Health, 2025)
IntroductionThe Stigma Assessment and Reduction of Impact (SARI) Stigma Scale is an instrument developed to evaluate stigma in Leprosy patients. Despite existing versions in Indonesian, the absence of an endemic area language version of a reliable assessment tool presents a barrier to effective interventions in regions like Ambon. This study aims to evaluate the validity and reliability of the Ambonese-Malay Language of SARI Stigma Scale questionnaire.MethodsA cross-sectional study involved 50 participants with leprosy or a history of leprosy from Ambon City, Indonesia. They were tested with the SARI Stigma Scale questionnaire, consisting of 4 domains of questions, totalling 21 questions. Reliability and variability analysis was conducted from each domain’s questions. Cronbach’s α (CA) and intraclass correlation coefficient (ICC) determined internal consistency of reliability tests. For validity assessment, coefficients of corrected item-total correlation ensured scale accuracy for measuring stigma.ResultsReliability analysis revealed significant high internal consistency (α and ICC value >0.7) across all four domains, with CA values ranging from 0.71 to 0.94 and strong consistency among responses, with ICC ranging from 0.71 to 0.94 across domains. The total domain exhibited a CA of 0.855 and an average ICC of 0.855 (p < 0.001). Validity testing demonstrated significant moderate to strong correlations, ranging from 0.69 to 0.90 (p < 0.001), affirming scale validity in measuring stigma accurately.DiscussionThe Ambonese-Malay version of the SARI Stigma Scale exhibits validity and reliability as an assessment tool for scoring stigma in leprosy patients in Ambon. Stigma can emerge and be associated with leprosy. To understand the stigma in society due to this disease, a validated questionnaire in the local language and adjusted with the local cultures needed.